The Denominational University and the New University Models: ¿Is possible to keep the identity? - Gregorutti, Gustavo (2012)
This study presents the dynamic relationship between the different mission statements and their impact on university’s models. The excessive promotion of the production of knowledge, as the central paradigm for higher education, has produced unbalances in universities. Religious affiliated institutions needs to reposition themself with their characteristics to offering an education that includes all three existing missions, but adds a fourth one as a way of enriching training. This new mission purpose that centers on the development of wisdom, it is not only useful for religious affiliated universities, but also for all kind of higher education models. Toward the end, the paper turns to some of the complications a more balanced model would face.